PFKFB3‐dependent glucose metabolism regulates 3T3‐L1 adipocyte development. Issue 7 (10th June 2021) - Griesel, Beth A.; Matsuzaki, Satoshi; Batushansky, Albert; Griffin, Timothy M.; Humphries, Kenneth M.; Olson, Ann Louise
Abstract: Proliferation and differentiation of preadipocytes, and other cell types, is accompanied by an increase in glucose uptake. Previous work showed that a pulse of high glucose was required during the first 3 days of differentiation in vitro, but was not required after that. The specific glucose metabolism pathways required for adipocyte differentiation are unknown. Herein, we used 3T3‐L1 adipocytes as a model system to study glucose metabolism and expansion of the adipocyte metabolome during the first 3 days of differentiation. Our primary outcome measures were GLUT4 and adiponectin, key proteins associated with healthy adipocytes. Using complete media with 0 or 5 mM glucose, we distinguished between developmental features that were dependent on the differentiation cocktail of dexamethasone, insulin, and isobutylmethylxanthine alone or the cocktail plus glucose. Cocktail alone was sufficient to activate the capacity for 2‐deoxglucose uptake and glycolysis, but was unable to support the expression of GLUT4 and adiponectin in mature adipocytes. In contrast, 5 mM glucose in the media promoted a transient increase in glucose uptake and glycolysis as well as a significant expansion of the adipocyte metabolome and proteome. Using genetic and pharmacologic approaches, we found that the positive effects of 5 mM glucose on adipocyte differentiation were specifically due to increased expression of 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐bisphosphatase 3 (PFKFB3), a key regulator of glycolysis and the ancillary glucose metabolic pathways. Our data reveal a critical role for PFKFB3 activity in regulating the cellular metabolic remodeling required for adipocyte differentiation and maturation.